Investigating the Causality Between Remittances, Infant Mortality, and Economic Growth in India: A Cointegration and Vector Error Correction Model Analysis - Hassan Rashid; Miguel D. Ramirez (Research in Applied Economics, 2024)
The main objective of this paper is to analyze the impact of remittances on human development as measured by infant mortality rates and real GDP per capita in India using time series data for the 1975-2018 period. By employing the Zivot-Andrews single-break unit root test and cointegration analysis using the Johansen procedure, a stable long-run relationship is found among the variables. Consequently, by estimating a VECM with dummy variables, results indicate that, in the long run, both remittances and real GDP per capita have a negative and significant impact on infant mortality rates in India. With infant mortality rate as a dependent variable, the adjustment coefficient for the cointegrating vector is negative and significant as the theory predicts. A Granger Block causality test is also conducted, and results indicate that remittances do not Granger cause real GDP and infant mortality rate; however, it is found that infant mortality rate and real GDP per capita Granger cause remittances. Policy implications are discussed.